Astroglial Plasticity Is Implicated in Hippocampal Remodelling in Adult Rats Exposed to Antenatal Dexamethasone. (4th August 2015) - Shende, Vishvesh H.; McArthur, Simon; Gillies, Glenda E.; Opacka-Juffry, Jolanta
Abstract : The long-term effects of antenatal dexamethasone treatment on brain remodelling in 3-month-old male Sprague Dawley rats whose mothers had been treated with dexamethasone were investigated in the present study. Dorsal hippocampus, basolateral amygdala and nucleus accumbens volume, cell numbers, and GFAP-immunoreactive astroglial cell morphology were analysed using stereology. Total brain volume as assessed by micro-CT was not affected by the treatment. The relative volume of the dorsal hippocampus (% of total brain volume) showed a moderate, by 8%, but significant reduction in dexamethasone-treated versus control animals. Dexamethasone had no effect on the total and GFAP-positive cell numbers in the hippocampal subregions, basolateral amygdala, and nucleus accumbens. Morphological analysis indicated that numbers of astroglial primary processes were not affected in any of the hippocampal subregions analysed but significant reductions in the total primary process length were observed in CA1 by 32%, CA3 by 50%, and DG by 25%. Mean primary process length values were also significantly decreased in CA1 by 25%, CA3 by 45%, and DG by 25%. No significant astroglial morphological changes were found in basolateral amygdala and nucleus accumbens. We propose that the dexamethasone-dependent impoverishment of hippocampal astroglial morphology is the case of maladaptive glial plasticity induced prenatally.